Synthesis of (R)-coniine and (S)-coinicine via organocatalytic alpha-aminoxylation of an aldehyde - Kondekar, Nagendra B.; Kumar, Pradeep (Synthesis-Stuttgart, 2010)
A short and efficient synthesis of the indolizidine alkaloid (S)-coinicine has been achieved using organocatalytic sequential alpha-aminoxylation and Horner-Wadsworth-Emmons olefination of an aldehyde catalyzed by L-proline. Similarly, a common organocatalytic alpha-aminoxylation route has been developed for the asymmetric synthesis of both (R)-coniine and (S)-coinicine.
Keywords: hemlock alkaloids; organocatalysis; Proline; sequential reactions; synthesis